Dynamic Resource Assignment and Cooperative Relaying in Cellular Networks: Concept and Performance Assessment. (20th August 2009) - Doppler, Klaus; Redana, Simone; Wódczak, Michał; Rost, Peter; Wichman, Risto
Abstract : Relays are a cost-efficient way to extend or distribute high data rate coverage more evenly in next generation cellular networks. This paper introduces a radio resource management solution based on dynamic and flexible resource assignment and cooperative relaying as key technologies to enhance the downlink performance of relay-based OFDMA cellular networks. It is illustrated how the dynamic resource assignment is combined with beamforming in a macrocellular deployment and with soft-frequency reuse in a metropolitan area deployment. The cooperative relaying solution allows multiple radio access points to cooperatively serve mobile stations by combining their antennas and using the multiantenna techniques available in the system. The proposed schemes are compared to BS only deployments in test scenarios, which have been defined in the WINNER project to be representative for next generation networks. The test scenarios are well defined and motivated and can serve as reference scenarios in standardisation and research. The results show that the proposed schemes increase the average cell throughput and more importantly the number of users with low throughput is greatly reduced.